Integrasi Nilai-Nilai Islam pada Kurikulum Merdeka di SDN 160 Sukalaksana Cicadas Bandung - Ibnu Hanif Akbari; Nisrina Salsabila Dermawan; Revalina Salsa Agustin; Muhsin (Jurnal Dirosah Islamiyah, 2025)
The integration of Islamic values ​​into the Independent Curriculum in elementary schools is a strategic step in shaping the character and spirituality of students from an early age. The Independent Curriculum, which provides educational units with the flexibility to develop curricula tailored to local needs, opens up significant opportunities for strengthening Islamic values, not only limited to Islamic Religious Education subjects but also internalized in various aspects of learning. This effort is crucial considering the increasingly complex challenges of the times that demand a strong moral, ethical, and spiritual foundation for the younger generation. Through this integration, it is hoped that students will not only understand Islamic concepts theoretically but also be able to practice them in their daily lives, thus creating individuals who are knowledgeable, have noble character, and contribute positively to society. The research method used in this study is a qualitative descriptive analysis approach. This approach aims to gain a deep understanding of the phenomenon of the integration of Islamic values ​​into the Independent Curriculum in elementary schools through natural and contextual data collection. Data were collected through observation, in-depth interviews, and documentation, then analyzed descriptively to describe the patterns, meanings, and processes of integrating Islamic values ​​into learning. Data analysis was conducted systematically, starting from data reduction, data presentation, and drawing conclusions, so that the research results can provide a comprehensive picture of the implementation of Islamic values ​​in the elementary school environment. This study aims to analyze how SDN 160 Sukalaksana Cicadas integrates Islamic values ​​in the Independent Curriculum through character building in the elementary school environment. This school implements various religious activities regularly, such as reciting the Asmaul Husana and short surahs before classes begin, performing the Dhuha prayer every Friday, and holding a short sermon to deepen the understanding and practice of key character values ​​in everyday life. In addition, the school also holds Islamic Religious Education (PAI) performances every month and regularly commemorates Islamic Holidays (PHBI) as a form of spiritual strengthening for students. This character building approach is very much in line with the spirit of the Independent Curriculum, which emphasizes flexibility and contextualization of learning according to local needs. The research results show that educational success at SDN 160 Sukalaksana Cicadas is measured not only by academic achievement, but more so by behavioral changes and the formation of positive habits instilled in students. These findings indicate that integrating Islamic values ​​through character building can be an effective model for supporting the character and spiritual development of students in elementary schools.